Climate Characteristics of the Neogene Period - Gulomjon Is’hakov (Genius Journals, 2022)
In our previous articles, we have considered the climatic conditions of Central Asia, their characteristics before the Neogene. Today's article describes the climatic conditions, nature, flora, fauna, tectonic movements of the Neogene period, the main factors that led to climate change, and ways to prevent them. Most importantly, you will gain an understanding of the impact of the ancient Tethys Sea on the climate.
Keywords: Neogene; Miocene; Pliocene; Alpine